Analisis Sosiologi Hukum Islam Terhadap Aliran Sempalan: Ahmadiyah Qadiyani di Indonesia : Analasis Sosilogis,Aliran Sempalan, Ahmadiyah Qadiyani - Nursalam; Kurniati; Achmad Musyahid (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This article aims to expose and examine the Ahmadiyah Qadiyani breakaway group in Indonesia through the lenses of sociology and Islamic law. Social contact and religious teachings, which are a rich source of Islamic theological thinking and include Ahmadiyah, are factors in the rise of Islamic sects. The presence of Qadiyani Ahmadiyya in Indonesia has become an interesting subject for sociological and Islamic legal studies. This research aims to analyze this phenomenon using a sociological and Islamic legal approach. Through a literature review, this study reveals the social dynamics that emerged with the existence of Ahmadiyah Qadiyani in Indonesian society, as well as the response of Islamic law to this sect. By considering the historical and social context, this analysis highlights Muslims' various pros and cons towards Ahmadiyah Qadiyani and its impact on relations between believers in Indonesia. This research also explores the implications of Islamic law for treating Ahmadiyah Qadiyani, including fatwas and legal regulations governing their existence. Thus, this study provides in-depth insight into the social and legal complexities associated with such splinter flows in Indonesia.